(untitled) (ModaPalavra e-periódico, 2025)
This article aims to analyze the influence of audiences (imagined and perceived) present on the digital platform Instagram on social performances carried out by digital influencers who are followers of the Body Positive movement. To achieve it, the concepts of Dramaturgical Theory proposed by Erving Goffman were used, considering the particularities of social interactions mediated by digital technologies. Non-participant observation was carried out with five profiles of digital influencers who self-declared followers of the movement. The collected data was analyzed from the perspective of content analysis, in order to identify the points considered relevant to serve the imagined audience, and to interact with the perceived audience. It is concluded that social performances carried out in digital environments, when based on social empowerment, such as Body Positive, become more complex because they require coherence from social actors in adhering to the discourses, in the need to transmit engagement and knowledge of the cause to all audiences, and in the assertive adoption of protective strategies. Furthermore, the important role of digital influencers was highlighted both in promoting and maintaining agendas associated with social empowerment movements.